Selected health related fitness in female undergraduate students - Mohamed, Nazirah Gulam (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2009)
To describe and compare the health-related physical fitness of young females based on body mass index (BMI) classifications. Anthropometric indices, including height, weight, waist and hip circumferences were assessed in a cross-sectional study of35 healthy female undergraduate students aged 20-22 years. Blood pressure was measured using a sphygmomanometer, while cardiorespiratory fitness (CRF) was estimated using the 20m multi-stage fitness test. The BMI of the students was classified according to cut-off points for Asians and two groups were identified: underweight (n= 10) and normal weight (n= 25). Between the BMI groups, weight (p = 0.001, eta2 = 0.297), percent body fat (p < 0.001, eta2 = 0.442), waist girth (p = 0.004, eta2 = 0.225), hip circumference (p = 0.006, eta2 = 0.208), and maximum heart rate (p = 0.001, eta2 = 0.301) were significantly different. However, there was no difference in height (p = 0.390, eta2 = 0.022), waist-to-hip ratio (p = 0.225, eta2 = 0.044) and aerobic fitness (p = 0.348, eta2 = 0.027). Both underweight and normal weight groups had a higher percent body fat and lower V02 peak than the recommended levels. These results support and extend previous studies that Asians have a higher body fat percentage at the same BMI level as Caucasians.